UUM golfers rule: Thaznim, Wafiyuddin and Amirul make a clean sweep in men's event - Tan, Karr Wei (The Star, 2013)
UNIVERSITI Utara Malaysia (UUM) made a clean sweep of the men's individual category during the Higher Education Institute Golf Tournament 2013 held at the Rahman Putra Golf Club in Sungai Buloh.